Respuesta :
Answer:
They are 3, 11 and 55.
Step-by-step explanation:
x +y + z = 69
y = x - 8
z = 5x
Substitute z = 5x in the first equation:
x + y + 5x = 69
6x + y = 69.........(1)
From the second equation
-x + y = -8.........(2)
Subtract equations (1) - (2):
7x = 77
x = 11
So z = 5x = 5*11 = 55 and
y = x - 8 = 11 - 8 = 3..
Answer:
x = 11, y = 3 and z = 55
Step-by-step explanation:
Let the three numbers be x, y and z. Then x + y + z = 69
Then y = x - 8, and z = 5x. Substituting these expressions in x into
x + y + z = 69, we get: x + x - 8 + 5x = 69, or
7x = 77, so that x = 11.
If x = 11, then:
y = x - 8 = 11 - 8 = 3, and:
z = 5x = 5(11) = 55
Then x = 11, y = 3 and z = 55.
Check: Do these three numbers add up to 69? 11 + 3 + 55 = 69? YES